Plyometric intervention in the UKM setting: An experimental analysis of three components of student physical condition - Iskandar, Risfan; Hariyanto, Agus; Setijono, Hari; Turi, Moh (Edelweiss Applied Science and Technology, 2025)
The increasing sedentary lifestyle among students is becoming a global health problem that impacts physical, mental, and productivity fitness. This study aims to test the effectiveness of plyometric exercises in improving agility, leg muscle strength, and reaction speed of students in the context of sports SMEs. This study used a quasi-experimental design with a Nonequivalent Control Group Design involving 30 male students aged 19-20 years. Subjects were divided into two treatment groups with variations of plyometric exercises: hexagonal exercises and lateral jumps (K1), and barrier jumps and skater jumps (K2). The training was carried out for eight weeks, three times a week. Measurements were made using the Illinois Agility Test, jump MD, and Whole Body Reaction. The results showed a significant improvement (p < 0.001) in all physical variables in both groups, with the results being most prominent in the K1 group. In conclusion, plyometric exercises are effective in improving aspects of student fitness and can be integrated into SME training programs in general. These findings make an important contribution to the development of science-based training modules in an efficient and workable campus environment.